Evaluation of Nutritional and Microbiological Properties of a Beverage Made from Baobab (Adansonia digitata): Evaluation of Nutritional and Microbiological Properties of a Beverage Made from Baobab (Adansonia digitata) - Adeniji, Paulina O.; Eyinla, Toluwalope E.; Olayanju, O. (Journal of Home Economics Research, 2024)
The objective of this study was to evaluate nutritional and microbiological properties of beverage made from baobab (adansonia digitata). Specifically, the study evaluated proximate content of beverage made from baobab fruit pulp (Adansonia digitata), assessed mineral composition of beverage made from baobab fruit pulp (Adansonia digitata), determined microbiological properties of beverage made from baobab fruit pulp (Adansonia digitata). A laboratory based experiment was applied to prepare and analyze samples of the Baobab drink. The results revealed that, even though, the drink had a high moisture content (83.69g) it could supply energy from carbohydrates (12.49g) and contained fat and protein in smaller amounts. Mineral composition was substantial for most nutrients but exceptionally high for potassium (5700ppm). The microbiological properties show that comparatively, the Baobab drink’s microbial status was within safe levels. However, the presence and absence of high moisture in drink and powder influenced the microbial load and isolates from both products respectively. It was recommended that the need to carry out consumer acceptance studies on the drink to guarantee adoption among baobab drinking growing populations. Also a scale-up of this drink to provide healthier replacements for sugar sweetened beverages.